4 - La gouvernance des universités au Sénégal : une grande réforme, mais pas une rupture - Diouf Diène Colly Ousseynou (Journal of Higher Education in Africa, 2022)
The present article proposes a reflection on the notion of continuity in the governance of universities in Senegal with the creation of 3 new ones ; and correlatively on the dimension of different management strategies related to it. Indeed, implementation of Information and communication technology for education ICTE strategies used by different universities of Senegal and the introduction of the Licence-Master-Doctorat LMD system can be explained through the genesis of these organizations, but also the diversity of governance. The objective of this research is to try to realize, these dynamic strategies implemented depending on the university. This is from the first of the differences in the statutes and operational modes of Senegalese universities, to explain this diversity strategy. This work therefore focuses on an understanding of the strategies and mode of functioning of each university ; But also on the modes of governance of the universities as a whole and their effects, to come up with proposals. The research is based on case studies of Senegalese universities, to give to see the consequences of this mode of diversity of Senegalese universities. Secondary data were first collected. 41 semi-structured interviews were conducted, and 12 were selected and subjected to qualitative analysis.